Twin-to-Twin Transfusion Syndrome: Prenatal Diagnosis and Treatment - Benoit, Richard M.; Baschat, Ahmet A. (American Journal of Perinatology, 2014)
Clinical Problem Twin-to-twin transfusion syndrome (TTTS) increases perinatal morbidity and mortality for 10 to 15% of monochorionic (MC) gestations.Pathophysiology MC gestations are at risk due to the angioarchitecture of the shared placenta, with anastomoses of varying type, size, and quantity. TTTS results from progression of a chronic perfusion imbalance across unbalanced placental anastomoses, typically arising between 15 and 26 weeks gestation. The resulting abnormal fetal blood volume levels and compensatory physiological responses lead to an increased risk for fetal death, end-organ damage, and preterm birth.Prenatal Diagnosis Surveillance with ultrasound is essential for detection and treatment. TTTS is diagnosed once polyhydramnios occurs in the recipient (maximal vertical fluid pocket [MVP] > 8 cm) and oligohydramnios in the donor (MVP < 2 cm). The Quintero et al method is commonly used for staging, utilizing the presence or absence of donor bladder filling, abnormal fetal Doppler values, fetal hydrops, and demise.Treatment Fetoscopic laser photocoagulation of placental anastomoses is an effective treatment addressing the underlying pathophysiology. Further research is needed to improve survival rates, reduce risks of fetoscopy, and gain understanding of the prediction, assessment, and optimization of long-term outcomes for TTTS survivors.
Keywords: twin-to-twin transfusion syndrome; prenatal diagnosis; monochorionic twins; fetoscopy; laser ablation